Getting Past the Rhetoric #2: Managing for ‘Thinking and Working Politically’ in Large Facilities - Tyrrel, Lavinia (Abt Associates - Governance Soapbox, 2018)

Getting Past the Rhetoric #1: Tendering for ‘Thinking and Working Politically’ in Large Facilities - Tyrrel, Lavinia (Abt Associates - Governance Soapbox, 2018)

Implementing adaptive management: A front-line effort — Is there an emerging practice? - Teskey, Graham; Tyrrel, Lavinia (Working Paper, 2021)
Among the many principles that currently inform donor-funded development initiatives, three appear to stand out: they should be politically informed, locally led, and adaptive. There is as yet little practical guidance for aid implementers regarding how to operationalise these approaches. What will it take to shift practice away from linear and planned approaches, towards models which foster local leadership and which engage with emergent and complex systems? This paper suggests that the answer is not to throw out the discipline of the logical framework, results frameworks, or theories of change. Rather they need to be handled rather more reflectively and ‘elastically’. The purpose of this paper is to set out how this can be achieved, and to propose 15 tools for donors, implementors and front-line staff to apply adaptive management (AM) in practice, at critical stages of the project cycle and within the dominant aid paradigm. This is what we are calling PILLAR: politically informed, locally led and adaptive responses. We are framing PILLAR to cover the full project cycle (design, implementation and review), hence the nomenclature of an ‘end to end’ approach. Our hope is that these tools will eventually replace the current planned, log-frame driven and top-down approach to aid design and delivery which dominates the development sector.

Dealing with uncertainty: Reflections on donor preferences for pre-planned project models - Tyrrel, Lavinia; Cole, William (Working Politically in Practice, 2016)
Keywords: IMPORTANT

Thinking and working politically in large, multi-sector Facilities: lessons to date - Teskey, Graham; Tyrrel, Lavinia (Governance Working Paper 2, 2017)

Monitoring, Evaluation and Learning for Complex Programs in Complex Contexts: Three Facility Case Studies – Governance Soapbox - Davda, Tara; Tyrrel, Lavinia (Abt Associates - Governance Soapbox, 2019)

Monitoring, Evaluating and Learning for Complex Programs in Complex Contexts: Three Facility Case Studies - Davda, Tara; Tyrrel, Lavinia (Governance Working Paper 6, 2019)

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

Managing Facilities: a stock-take from the first 12 months - Tyrrel, Lavinia; Teskey, Graham; de Lacy, Jacqui (Governance Working Paper 3, 2017)

Reflections on implementing politically informed, searching programs: lessons for aid practitioners and policy makers - Cole, William; Ladner, Debra; Koenig, Mark; Tyrrel, Lavinia (Working Politically in Practice, 2016)